Ordinary language semantics: the contribution of Brentano and Marty. Issue 4 (3rd July 2020) - Taieb, Hamid
ABSTRACT: This paper examines the account of ordinary language semantics developed by Franz Brentano and his pupil Anton Marty. Long before the interest in ordinary language in the analytic tradition, Brentanian philosophers were exploring our everyday use of words, as opposed to the scientific use of language. Brentano and Marty were especially interested in the semantics of (common) names in ordinary language. They claimed that these names are vague, and that this is due to the structure of the concepts that constitute their meaning: concepts expressed by such names are themselves vague, based on typicality, and have more or less similar items within their extension. After presenting the views of Brentano and Marty, this paper compares them to later accounts of meaning and concepts, notably Wittgenstein's theory of family resemblances and the prototype theory of concepts, and emphasizes the originality of the Brentanian position.